2013
DOI: 10.1186/2049-3002-1-20
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic demands of cancer cells are coupled to their size and protein synthesis rates

Abstract: BackgroundAlthough cells require nutrients to proliferate, most nutrient exchange rates of the NCI60 panel of cancer cell lines correlate poorly with their proliferation rate. Here, we provide evidence indicating that this inconsistency is rooted in the variability of cell size.ResultsWe integrate previously reported data characterizing genome copy number variations, gene expression, protein expression and exchange fluxes with our own measurements of cell size and protein content in the NCI60 panel of cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
177
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(195 citation statements)
references
References 35 publications
17
177
0
1
Order By: Relevance
“…One reason for this stressed state is that the cancer cells are rapidly dividing and require the quick generation of large numbers of proteins. 6 When these proteins are not folded fast enough unfolded proteins accumulate, which triggers a 'heat shock response' (HSR). 7 A HSR is depicted in Figure 2 and summarized below.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this stressed state is that the cancer cells are rapidly dividing and require the quick generation of large numbers of proteins. 6 When these proteins are not folded fast enough unfolded proteins accumulate, which triggers a 'heat shock response' (HSR). 7 A HSR is depicted in Figure 2 and summarized below.…”
Section: Introductionmentioning
confidence: 99%
“…Dioxoisoindolin-2-yl)-3-(5-hydroxy-1H-indol-3-yl)propanoic acid(2). To a solution of 5HTP 1 (1 equiv, 4.73 g, 21.49 mmol) and phthalic anhydride (1 equiv, 3.18 g,21.49 mmol) in DMF (53.7 mL), triethylamine (1.6 equiv, 4.8 mL, 34.4 mmol) was added and the mixture was heated to 140 °C where complete dissolution occurred.…”
mentioning
confidence: 99%
“…103 Consequently, the demand for amino acids-the building blocks of proteins-is increased. In this regard, studies have demonstrated that many types of tumor cells have significantly increased L-type amino acid transporter 1 (LAT1) expression, which is the major transporter of large neutral amino acids.…”
Section: Imaging Protein and Cell Membrane Metabolismmentioning
confidence: 99%